The Relationship between Sharia Compliance and Profitability: A Study of Sharia Commercial Banks in Indonesia - Siti Fajriah Azizah; Rafika Rahmawati; Purnama Putra (SAN Scientific, 2026)
This study aims to analyze and compare the financial performance of Islamic Commercial Banks in Indonesia using the Sharia Conformity and Profitability (SCnP) method. Sharia Conformity measures a bank's level of compliance with sharia principles, while profitability assesses a bank's ability to generate profits. The data used are the financial performance reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK) in 2023. SCnP indicators include sharia-compliant product structures and compliance with the National Sharia Council (DSN) fatwas, while profitability is assessed through Return on Assets (ROA) and Return on Equity (ROE). The results show that Bank Muamalat Indonesia and Bank Aceh Syariah are in the URQ quadrant, with Sharia Conformity levels of 75% and 79%, respectively. In terms of profitability, Bank Aceh Syariah performed 67.15% higher than Bank Muamalat Indonesia at 1.37%. This finding indicates a positive correlation between sharia compliance and profitability, where increased sharia conformity can strengthen financial performance. The implications of this research emphasize the importance of strategies that focus on sharia compliance to support the growth and competitiveness of sharia banks in Indonesia.